2018
DOI: 10.1099/ijsem.0.002749
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the diversity of the honeybee gut symbiont Gilliamella: description of Gilliamella apis sp. nov., isolated from the gut of honeybees (Apis mellifera)

Abstract: The gut microbiota of honeybees (Apis) and bumblebees (Bombus) include the symbiotic bacterial genus Gilliamella. This genus shows a high degree of functional and genomic diversity and separates into distinct lineages. Gilliamella apicola wkB1, which was isolated from Apis, was the first species to be described. Recently four new species, isolated from Bombus, were identified. In this paper, we compare several genomes/strains from previous studies spanning this diversity, which gives insight into the phylogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 22 publications
1
28
0
Order By: Relevance
“…Although Gillamella are not classified as LAB, they provide similar functions. Studies have reported that Gillamella apicola were fermentative bacteria in the honey bee’s gut and supported hosts in the utilization, fermentation and uptake of some essential sugars that were indigestible by bees [ 45 , 46 , 47 ]. Similar to Lactobacillus and Bifidobacterium , Gillamella have been shown to protect hosts from pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Although Gillamella are not classified as LAB, they provide similar functions. Studies have reported that Gillamella apicola were fermentative bacteria in the honey bee’s gut and supported hosts in the utilization, fermentation and uptake of some essential sugars that were indigestible by bees [ 45 , 46 , 47 ]. Similar to Lactobacillus and Bifidobacterium , Gillamella have been shown to protect hosts from pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…As known, intestinal symbionts of insects inhibit the action of pathogens. The main symbiont bacteria, Snodgrassella alvi [86] and Gilliamella [87], were studied in the body of Apis mellifera and Bombus sp. It turned out that bees contain a greater number of bacterial strains than bumblebees, which confirms the hypothesis that the foundation of colonies by swarms of workers allows to keep a greater diversity than the foundation of colonies by one queen.…”
Section: Microbiome Of Bumblebees and Honey Bees And The Impact Of Pementioning
confidence: 99%
“…From a taxonomic perspective, the extensive intra-phylotype diversity has resulted in some phylotypes now harboring multiple named species, and others harboring highly divergent lineages with the same species name 22 . Naming of species within phylotypes has so far mostly been motivated by divergence in the non-ribosomal part of the genomes and the aforementioned differences in metabolic profiles 23 , but also on ANI 24 . However, the natural population structure within phylotypes has not been systematically investigated, and it is unclear to what extent the named species represent discrete evolutionary lineages (SDPs).…”
Section: Introductionmentioning
confidence: 99%